PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. MEGA PERSADA INDONESIA (STUDI KASUS PROYEK DASWIN OFFICE TOWER) - Markiz Yudiawan; Sismiati Sismiati; Rizal Rahmawan (Bajang Institute, 2023)
This study aims to analyze and determine the effect of leadership on the performance of employees of PT. Mega Persada Indonesia on the Daswin Office Tower project. The population in this study were employees of PT. Mega Persada Indonesia in the Daswin Office Tower Project numbered 43 peoples. Data were processed using IBM SPSS version 25. The results showed that leadership influences employee performance with a tcount = 4.908> ttable = 2.020 or significant count = 0.000 < of α = 0.05. The great influence of leadership on the performance of employees of PT. Mega Persada Indonesia in the Daswin Office Tower project is 0.370 or 37%, while the remaining 63% is influenced by other factors